2019
DOI: 10.1002/cche.10223
|View full text |Cite
|
Sign up to set email alerts
|

Glucose release from lentil flours digested in vitro: The role of particle size

Abstract: Background and objectives: Regular intake of pulses has been shown to offer numerous health benefits, including improved glycemic control. The objective of this study was to investigate the in vitro carbohydrate digestion rate of raw, baked, and moist-heat cooked lentil flours of varying particle sizes: coarse (710-1,190 μm), regular (355-710 μm), fine (180-355 μm), very fine (80-180 μm), and superfine (<80 μm) over 180 min using the Englyst method. Findings: There was an effect of particle size (p < .05), tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…These values are higher than those reported for baked navy bean flour by Luhovyy et al. (2017), perhaps due to the higher moisture content in the current study, but they are similar to the values reported by Kathirvel et al., (2019) for baked lentil flours. Since 41% of the starch in the large fraction was from broken cells, if it hydrolyzes to the same extent (72%) as the small fraction it would account for a starch hydrolysis value of 29.5% based on the total starch content.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These values are higher than those reported for baked navy bean flour by Luhovyy et al. (2017), perhaps due to the higher moisture content in the current study, but they are similar to the values reported by Kathirvel et al., (2019) for baked lentil flours. Since 41% of the starch in the large fraction was from broken cells, if it hydrolyzes to the same extent (72%) as the small fraction it would account for a starch hydrolysis value of 29.5% based on the total starch content.…”
Section: Resultssupporting
confidence: 76%
“…(2019) measured the particle size distribution in commercially milled split yellow pea, whole navy bean, and decorticated red lentil flours, and found that the volume‐weighted mean particle size was ~248 µm in regular flours and ~131 µm in fine flours. Starch digestibility has also been shown to decrease with increasing particle size for baked navy bean flour (Luhovyy et al., 2017) and baked lentil flour (Kathirvel et al., 2019). We are not aware of any study examining the effects of particle size on the digestibility of pulse proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The protein content of GL and YP flours varied between 24.8%-26.5% and 22.4%-26.2%, respectively. However, there was no particular trend regarding particle size and protein content which is in agreement with the results of Kathirvel et al (2019), who could not observe a trend between protein content and particle size of lentils varying from superfine (<80 µm) to coarse (710-1,190 µm). The starch content ranged from 48% to 57% with higher starch contents observed in break flours in both pulses.…”
Section: Flour Characteristicssupporting
confidence: 90%
“…reported as 9.7% (Setia et al, 2019). However, RDS values increased in lentil flours with decreasing particle size and superfine flours (<80 µm) had 14.2% RDS while very fine flours (80-180 µm) had 8.1% RDS (Kathirvel et al, 2019). Slowly digestible starch results were also found to be similar in all flour types for both GL (8.9%-9.4%) and YP (7.7%-8.5%) flours.…”
Section: In Vitro Starch Digestibilitymentioning
confidence: 78%
See 1 more Smart Citation